TRADISI ZIARAH KUBUR DI PULAU PAJENEKANG KABUPATEN PANGKEP PERSPEKTIF ISLAM - Rizky, Muh. Fajar; Mubakkirah, Fadhliah; Ubay (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
The tradition of grave pilgrimage has become a common practice among Muslims in Indonesia, including the community on Pajenekang Island, Pangkep Regency, South Sulawesi. This tradition includes rituals of visiting the graves of Islamic scholars who are considered to have contributed to the spread of Islam, as well as heroes who fought to protect the sovereignty of Pajenekang Island from Dutch colonizers. This practice is a heritage passed down from generation to generation. This study employs a qualitative-descriptive research method with an empirical juridical approach. The findings indicate that the tradition of grave pilgrimage on Pajenekang Island in Pangkep Regency integrates Islamic principles with local cultural customs. This includes rituals such as bringing specific traditional cakes to the gravesite and praying or performing tawassul near the grave. The pilgrimage is conducted on the third Friday of the month of Muharram. The study concludes that, based on the theory of ‘Urf and the principle of Al-‘Adatu Muhakkamah, the tradition of grave pilgrimage on Pajenekang Island is permissible (mubah) as it does not conflict with Islamic teachings. However, attention must be given to the intention and purpose of the pilgrimage to ensure that individuals do not fall into the practice of shirk (idolatry).